Polymer materials—challenges and hope - Kowalczuk, Marek (Frontiers in Soft Matter, 2023)
Polymer materials play an important role in various aspects of our lives. Most of them are solid, therefore, the key importance of such polymeric materials is related to their versatility, lightness, economy, durability and strength, corrosion resistance, electrical and thermal insulation (except conductive polymers), appropriate interface between the body and medical devices, and as well as design flexibility. In general, the importance of polymeric materials lies in their versatile properties, cost-effectiveness, and applicability in a variety of industries, including automotive, aerospace, electronics, healthcare, construction, packaging, and more. The purpose of this mini-review is to encourage future authors to submit outstanding contributions related to various aspects and frontiers of polymeric materials in the years to come.